Sexual intermediacy and temporality in late nineteenth- and early twentieth- century literature and culture - Funke, Jana (The University of Edinburgh, 2010)
It is often acknowledged that the sexually intermediate body destabilises sexual dimorphisms, but, so far, little attention has been paid to the way sexual intermediacy relates to normative figurations of time. Focusing mainly on literary and cultural discourses from late Romanticism to Modernism, the thesis examines how constructions of sexual intermediacy have contributed and responded to shifting concerns with temporality. It also investigates the relationship between literature and science through a comparative engagement with evolutionary, psychoanalytic and sexological discourses. The individual chapters deal with the conflicted temporality of the substantiated androgyne; the haunted and uncanny materiality of the hermaphroditic body in late nineteenth-century science and literature; sexual intermediacy and the prescriptive linear narrative of the case history; the sexual, temporal and national crises of World War I; and sexual travels in time and space. Overall, the thesis illustrates that sex and time are intimately related and shows that the changing understanding of sexual intermediacy opens up a powerful critique of sexual and temporal structures.
Keywords: sex; gender; time; 19th century; 20th century; literature; sexual intermediacy